Wicked wellbeing: Examining the disconnect between the rhetoric and reality of wellbeing interventions in schools. Issue 2 (August 2019) - Svane, Denise; Evans, Neus (Snowy); Carter, Margaret-Anne
Wellbeing is an emerging priority that poses a "wicked" problem. Current directives from policy makers are that schools address student wellbeing. However, the lack of a clear definition, simple solution or process for ensuring wellbeing creates a difficult task for schools. This article seeks to add to the current understanding of wellbeing in schools by drawing on the findings of a systematic literature review to investigate the characteristics and outcomes of school-based wellbeing interventions. Four databases were searched to identify relevant peer-reviewed articles published in English. The background discussion is set in the Australian context; however, the geographic scope of the literature review is international. Findings of the study align with previous research that views definitions of wellbeing as problematic. The broad range of wellbeing interventions found in the literature highlights a lack of consensus around best practice for wellbeing in schools. Despite evidence showing the benefits of a whole school approach, the majority of articles describe programmes and strategies targeted at small groups of students. The outcomes of the interventions are difficult to compare because they do not necessarily relate directly to wellbeing. This article raises questions about the evidence base to support the validity and trustworthiness of the interventions. Further research is necessary to consolidate understandings of wellbeing and to provide solid research evidence to inform further development of school wellbeing practices.